Assessment of quality of life and dietary practices of type 2 diabetes in Bharatpur Metropolitan, Chitwan. - Paudel, Sulaksha (2021)
ABSTRACT : Introduction: Diabetes Mellitus is a major cause of morbidity and mortality and places a huge strain on public health funding. Diabetes mellitus has reached epidemic proportions. According to the world health organization (WHO) there is an apparent epidemic of diabetes which is strongly related to the life style and economic changes. Quality of life (QOL) is also an important in the diabetes where it is the subjective wellbeing. Similarly, there is the role of appropriate dietary intake to control type 2 DM. Consumption of adequate amount of energy and nutrients is important to decrease high blood glucose level and to slow progress of the disease. The study aim was to assess the Quality of life and food consumption practices among type 2 diabetes patient and factors associated with food consumption practices. Methodology: Cross- sectional study was conducted among 236 participants from October 2019 to March 2020 among the diabetes type 2 patients of Bharatpur Metropolitan, Chitwan. Consecutive sampling techniques was used. Face to face interview was data collection technique and semi structured questionnaire was used as a tool for Assessment Of Quality of Life and Dietary Practices of Type 2 Diabetes in Bharatpur Metropolitan, Chitwan. The questionnaire was developed with consultation with supervisor on the basis of study variable which is obtained from extensive literature review. The Nepali version of the questionnaire was pre-tested among 10% i.e. 24 of total sample and its accuracy is measured before data collection. Ethical approval was obtained from Institutional review committee and maintained during the process of research. A set of questions adapted from Diabetes-39 was used as a tool for assessing the quality of life of the participants. The D-39 was translated into simple and clear Nepali language and was back translated into English language. The Nepali version of the D-39 instrument was pre-tested among 10% of total sample in homogenous area to test its accuracy before data collection. The collected data was entered in EPI-DATA which was exported to SPSS for further analysis. Data was analyzed based on the objective of the study. Results: This study found that half of the participants was from the age group 45-59 years. Among the participants, about three-fifth were female and rest was male. About three-fourth of the participants were Hindu, followed by Buddhist and Christian and majority of the participants were married. Half of the participants lived joint family and majority of the participants was literate. The main source is agriculture. Here majority of the participants don't eat sugar and boil rice. 76.3% of the participants eat normal non-vegetarian food and remaining rest of the participants eat vegetarian food. Only few number of the participants had dietary plan. Half of the participants don't eat sweets where all participants eat fruits and vegetable. Majority of the participants don't had smoking and drinking alcohol habits. Half of the participants eat medicine through tablets. 93.2% of the participants had good quality of life and half of the participants had poor dietary practices. Here sex and education is associated with the quality of life where religions, caste, marital status was not associated with the quality of the life. Dietary plan is also associated with the quality of life. Quality of life and dietary practices is not associated. Conclusion: This shows that half of the participants had good quality of life. Majority of the participants were in the age group 50-59 and also showed that half of the participants were female whereas nearly more than half of the female participated were married. The main source of income of the participants was Agriculture. During the morning meal half of the participant eat dal, khana and tarkari where as in dinner they used to eat dal, roti and tarkari. Half of the participant do physical activities and majority of the participants were suffering diabetes from more the 2 years and half of the participants don't ever miss the medication. And the dietary practices of the participant was poor because of the economic conditions and also they don't have any dietary plan.